Edukasi tentang Rendam Hangat untuk Menurunkan Tekanan Darah pada Ibu Preeklampsia - Pebrianti, Dwi Kartika; Kusuma, Ratu; Yuliana, Yuliana (Prosiding Seminar Kesehatan Nasional, 2024)
Preeclampsia is one of the main causes of deaths and the number of perinatal individuals in Indonesia. Until now, preeclampsia is still a obstetric problem that has not been completely solved. Preeclampsia is a disease whose incidence rate varies in each country. The aim of education is to reduce blood pressure in pregnant women at the Putri Ayu Health Center in Jambi City, they can do dysmenorrhoea exercises to prevent dysmenorrhoea pain. The activity began with a pretest, then education and demonstrations regarding warm soaking were carried out, then a posttest was carried out. The media used are posters, ppt, leaflets and questionnaires. The educational target was 10 respondents. This activity was carried out at the Putri Ayu Health Center in Jambi City over a period of 3-6 months in March 2024-July 2024. The results obtained before being given education, knowledge about warm soaking, respondents were less than 60%. After being given education, knowledge about warm soaking respondents was less than 10%. It is hoped that provide information to pregnant women about warm soaks regarding how to provide additional insight to increase pregnant women's knowledge about non-pharmacological therapy every month, namely warm soaks which aim to lower blood pressure. There has never been any education about warm soaks to reduce blood pressure in preclamptic mothers